Ulasan Tentang Hambatan Yang Dihadapi Mahasiswa Dalam Mempelajari Matematika - Mendrofa, Putra Sudi Selamat (CV. SINAR HOWUHOWU, 2025)
Mathematics is often considered a challenging subject for many students. Various obstacles, including psychological, cognitive, and contextual factors, can affect students' understanding and achievement in this subject. This study reviews the various barriers faced by students in learning mathematics, such as a lack of motivation, difficulty in understanding abstract concepts, and an inability to relate theory to practical applications. Additionally, factors such as stress, fear of failure, and the quality of teaching also play a role in exacerbating the situation. To overcome these barriers, it is recommended that mathematics instruction be more tailored to students' needs, incorporating more interactive teaching methods, and creating a supportive environment that reduces anxiety toward the subject.